1980
DOI: 10.1172/jci109976
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane and Stable Prostaglandin Endoperoxide Analogs Stimulate Water Permeability in the Toad Urinary Bladder

Abstract: A B S T R A C T The effects of thromboxane B2 and the stable prostaglandin endoperoxide analogs (15Z)-hydroxy -9a -1 la -(epoxymethano)prosta -5Z,13E -dienoic acid (U44069) and (15Z)-hydroxy-1 la,9a-(epoxymethano) prosta-5Z,13E-dienoic acid (U46619) were tested on water flow across the toad urinary bladder. In the presence of indomethacin or meclofenamic acid, inhibitors of prostaglandin and thromboxane A2 synthesis, thromboxane B2 stimulated water flow in a dose-dependent manner. U44069 (1 gM) stimulated wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
1
1
1
1
Order By: Relevance
“…However, the authors of those reports do not provide a clear indication as to whether the effects of TXB2 are exerted at the site of or distal to cyclic AMP generation. BURCH and HALUSHKA (1980) observed that TXB2 alone stimulated the water flow in the toad bladder, though we were unable to do so. We found TXB2 to enhance vasopressin-stimulated water flow but to have no effect on cyclic AMP-stimulated.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, the authors of those reports do not provide a clear indication as to whether the effects of TXB2 are exerted at the site of or distal to cyclic AMP generation. BURCH and HALUSHKA (1980) observed that TXB2 alone stimulated the water flow in the toad bladder, though we were unable to do so. We found TXB2 to enhance vasopressin-stimulated water flow but to have no effect on cyclic AMP-stimulated.…”
Section: Discussioncontrasting
confidence: 61%
“…ZUSMAN et al (1977) were the first to report that vasopressin stimulates PGE2 biosynthesis in the toad bladder, and that 1 mU/ml vasopressin increases PGE2 synthesis from 0.5 + 0.1 pmoles/min • hemibladder to 5.0 + 0.4. In a recent study, it was found that when PGE2 biosynthesis in the toad bladder was at a basal level of 0.22 + 0.01 pmoles/min • hemibladder, it was stimulated 5 times as much as by Japanese Journal of Physiology vasopressin (BURCH et al, 1980) and when at a basal level of 0.27 + 0.05 pmoles/ min mg prot., it was stimulated by 5 mU/ml vasopressin to 0.53 + 0.09 (BURCH and HALUSHKA, 1982). After removing the bladder from the toads, a preparatory period of no more than 2 h is necessary prior to the start of the experiment.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, OKY-1581 suppressed the vasopres sin-induced osmotic water flow in the toad bladder at 1 X 10~6 M, but enhanced it at 1 X 10-4 M. Burch and Ilalushka [ 16] reported that TXB2 enhanced the vasopressin-induced water flow. Since PGA2 is produced in the load bladder [11,16], the effect of OKY-1581 at low concentration can be explained as arising from its inhibitory' effect on throm boxane synthetase.…”
Section: Discussionsupporting
confidence: 54%
“…L'agrégation plaquettaire est un phénomène réversible (111). On a suggéré que la TXA sert de médiateur à l'action de l'ADH (216).…”
Section: La Tx Aunclassified